Direct laser micro-drilling of high-quality photonic nanojet achieved by optical fiber probe with microcone-shaped tip; Applied Physics A; Vol. 131, iss. 1 - Li Lieber Po-Hung; Hung Ting-Yuan; Wei-Yu Chen; Hung-Ju Chung; Chia-Hsiung Cheng; Tien-Li Chang; Chen Yu-Bin; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich; Cheng-Yang Liu (2024, 2024)
Title screen